2018
DOI: 10.18268/bsgm2018v70n2a12
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous Roveacrinids from Mexico revisited: Overcoming the taxonomic misidentifications and subsequent biostratigraphic abuse

Abstract: The Mesozoic carbonate deposits of Mexico yield a number of overlooked, ill-known, and even enigmatic microfossils, among which are roveacrinoids (Echinodermata, Crinoidea, Roveacrinida). Most of these pelagic organisms probably came from the central Tethysian seaways, and later on from the early central Atlantic Ocean through the northwestern Tethysian neck, thus reaching the Central American platforms (Comanchean shelf, Central Texas platform, and Coahuila platform) and the Western Interior seaway. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…With the exception of the so-called Microcalamoides used for slanted ancillary dating [Microcalamoides Bonet, 1956, is the morphological variant thecal sections of Applinocrinus Peck, 1973, ranging from Aptian to Maastrichtian, thus invalidating any precise datation. For review see Ferré et al (1997Ferré et al ( , 2018], no saccocomid remain has ever been reported so far in Mexican Albian deposits and/or elsewhere in the Gulf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the so-called Microcalamoides used for slanted ancillary dating [Microcalamoides Bonet, 1956, is the morphological variant thecal sections of Applinocrinus Peck, 1973, ranging from Aptian to Maastrichtian, thus invalidating any precise datation. For review see Ferré et al (1997Ferré et al ( , 2018], no saccocomid remain has ever been reported so far in Mexican Albian deposits and/or elsewhere in the Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of the so-called Microcalamoides used for slanted ancillary dating of Mexican Cretaceous strata [Microcalamoides Bonet, 1956, is the morphological variant thecal sections of Applinocrinus, ranging from Aptian to Maastrichtian, thus invalidating any precise datation (for review, see Ferré, 1997;Ferré et al 1997Ferré et al , 2018], no saccocomid remain has ever been reported so far in Mexican Albian deposits and/or elsewhere (only roveacrinids; for review, see: Rasmussen, 1961;Destombes, 1985;Dias-Brito, 1994Dias-Brito & Ferré, 1994, 2001Ferré & Granier, 2001). This relatively restricted occurrence zone of such saccocomid microfacies, very different from the standard Microcalamoides Zone, is consistent with one of the OAE1 hypoxic events.…”
Section: Stratigraphical Inference/ Perspectives and Potentials/age Omentioning
confidence: 99%